Analysis of Non-Performing Loans Indicators and Their Treatment in The Kurdistan Region – Iraq: A Practical Study Of Sample Of Banks For 2019. - Sardar Othman Badawaiy; Karkhi Khalid Sabah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The study aims to identify the indicators of non-performing loans of banks working in the Kurdistan Region-Iraq, and provide appropriate solutions to solve this problem and try to avoid NPLs in the future, and the study has reached a range of results, including: We conclude that there is corruption in the higher management of banks and use public position to serve the private interests, which is one of the reasons for the NPLs, due to the administrative and financial corruption in the Kurdistan Region. The ratio (37.5%) of the working banks believes that there is bad faith in the borrowers and unwillingness to pay their debts despite their ability to refund. The ratio (34.56%) of the working banks did not study the borrower’s good reputation. The ratio (30.06%) of the working banks believe that the borrowers did not do thorough study in expanding their investment activity. NPLs in the working banks in the Kurdistan Region have been caused by the emergence of Daash in Iraq and bad economic management by the Kurdistan Region government led to the emergence of the financial crisis in the Kurdistan region and then impose a system of saving on staff. The study concluded with a number of suggestions: The lack of intervention by senior management in the process of granting loans, and away from social considerations. After stage of the float, Resuscitation and pull out the borrower, the courts and Jurisdictions are the best option available to the working banks to processing the NPLs. Access of private banks to the movable and immovable property of the Government of against its NPLs. Implement effective banking systems in the area of credit monitoring and follow up. Granting loans by banks in the form of payments and according to the actual needs of the borrower.